Peran Norma Sosial dalam Mendorong Kepatuhan Hukum - Ghozali Boer, Achmad Dirham; Dinanti, Dinda (Media Hukum Indonesia (MHI), 2025)
This study examines the role of social norms in encouraging public compliance with the law. Social norms are unwritten rules that develop from habits, values, and cultural practices that exist within society. In many cases, social norms are obeyed more readily than formal laws because they are more closely connected to everyday life. This research uses a literature study method by analyzing works related to the sociology of law, social norms, and legal compliance. The results show that legal compliance does not arise solely from the threat of formal sanctions but also from the internalization of values and norms obtained through socialization processes. When social norms align with the law, the level of public compliance increases. However, if social norms conflict with the law, legal violations are more likely to occur. Thus, it can be concluded that social norms have an important role in building a legal culture and enhancing public compliance with legal rules in Indonesia.